Respiratory health in a total very low birthweight cohort and their classroom controls. Issue 3 (March 1996) - McLeod, A; Ross, P; Mitchell, S; Tay, D; Hunter, L; Hall, A; Paton, J; Mutch, L
Abstract : AIMS: To compare the respiratory health and function at 8 to 9 years of age of a total population based cohort of 300 very low birthweight (VLBW) children with that of two classroom controls (n = 590) matched for age and sex. STUDY DESIGN: Cohort study with controls. SETTING: Schools throughout Scotland. RESULTS: The VLBW children were more likely than their peers to use an inhaler, to be absent from school, and to be admitted to hospital because of respiratory illness. They were significantly shorter than their classroom controls, but even after adjusting for differences in height, the VLBW children had reduced forced vital capacity (FVC); this was associated with a history of prolonged ventilation (> 28 days) and pneumothorax in the neonatal period. There were no significant differences between the groups in forced expiratory volume in one second (FEV1)/FVC but twice as many (7.9% v 3.7%) of the VLBW children had ratios < 70%, denoting obstructive airways disease. Poor expiratory function was associated with neonatal respiratory distress syndrome, prolonged ventilation, and the need for > 40% oxygen. Exercise induced airway narrowing was increased in VLBW children (odds ratio = 2.0; 95% confidence interval 1.2 to 3.4) and was very little changed by adjustment for inhaler use and exposure to cigarette smoke. CONCLUSIONS: As in other low birthweight cohorts, respiratory morbidity was increased. Unlike previous studies, FVC was more affected than expiratory function in this VLBW population. Our findings support the hypothesis that poorer lung function is associated with very low birth weight, but not with intrauterine growth retardation.